Desenvolvimento do conhecimento físico com a aprendizagem baseada em problemas : análise das interações discentes - Soares, Vando Kleber Santos (2017)
This work investigated the establishment of the interactive process among the students of a third grade high school class with the adoption of the methodology of problem-based learning (PBL) and its relation in the development of students' scientific and everyday concepts about electrodynamics. The research was carried out at a state public high school in the interior of the state of Sergipe. In order to analyze social interactions, we used Vygotsky's ideas, Wertsch's (1984) constructs, from Monteiro's (2006) perspective, and the (2002) Analytical tool of Mortimer and Scott. Participant observation was used for data collection, which was performed during 11 classes, and a recorder was used to record the conversations of two groups. Field records, evaluation chart, knowledge sheets and tests of the students were also used. The results showed that the PBL allowed the students to formulate and to expose their points of view of the studied contents, which promoted the emergence of interactive chains as a pattern of interaction and to use semiotic resources as mediators for the understanding and development of the concepts.